Tradisi Pupak Puser: Implementasi dan Makna Simbolik Kearifan Lokal di Desa Takeranklating Kecamatan Tikung Kabupaten Lamongan - Sholihah, Titis Khoiriyatus; Robikhah, Aridlah Sendy (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The pupak puser tradition is where the baby experiences the release of his umbilical cord and a pupak navel will be held. From the results of this traditional research, the implementation time of the pupak puser tradition is at night after the Isha prayer on the day after the baby's umbilical cord is separated from the navel. This market ceremony is a form of gratitude for the blessings and salvation God Almighty gave to the baby and the mother. This research aims to raise the issue into a scientific work so that it is widely known by the public and the writers who are studying. This study uses qualitative research using ethnographic methods and data collection techniques that are shown and proven by interviews, documentation, observation, and so on. The history of the implementation of the Pupak Puser Tradition in Genceng, Tikung, Lamongan Regency is one of the hamlets belonging to the religious community. This tradition was born in the ancestors' time and is still developing almost until now. This tradition was carried out long ago by the elders. This tradition ensures that the baby is always given health and safety.